A literature review of historical trends and emerging theoretical approaches for developing sustainable cities (part 1). (16th December 2015) - Bayulken, Bogachan; Huisingh, Donald
Abstract: Spatial and urban development policies and trends have changed extensively since industrialization began in the early 1800s. Policies that were based on economic growth along with rapid urban population increases in the 20th century irreversibly and negatively impacted most urban eco-systems globally. Climate changes began to occur mainly due to fossil carbon intensive technologies upon which the urban systems and lifestyles have co-evolved. Concepts such as sustainable development (SD) and ecological modernization (EM) were among the most discussed approaches with regard to ways of responding positively to the emerging environmental concerns induced by the growth policies and development strategies. In spite of some positive contributions to urban policies that resulted in relative successes, most notably in Northwest Europe, questions remained as to whether these concepts have effectively and sufficiently catalyzed the promotion of sustainable urban developments more broadly. By building this literature review, the authors explored the evolutionary aspects and the shortcomings of the EM and SD within the overarching sustainability paradigm. The review addressed the emerging theories developed to improve approaches to urban development policies and procedures, and to contextualize the evolution of regenerative or net positive developments in broader cultural, geographical and temporal contexts. The historically significant antecedents were reviewed and visions for needed transitions were outlined in this two-part series of review articles. Highlights: Urbanization processes and trends, after industrialization began in 1800s, were reviewed. The strengths and shortcomings of Ecological Modernization and Sustainable Development were discussed. The evolutionary concepts within the overarching sustainability paradigm were reviewed. Alternative transitional and operationalized sustainability concepts were highlighted. Synergistic and integrative approaches to improve urban development policies were emphasized.